(untitled) (Bangladesh Journal of Urology, 2020)
Background: Percutaneous nephrolithotomy (PCNL) is a common procedure for the removal of renal stones larger than 2 cm size with the advantages of lower morbidity rates, decrease in post-operative pain with faster post-operative recovery & thereby less duration of postoperative hospital stay. One of the fundamental steps of PCNL is the creation of the nephrostomy access. It can be done either by single shot dilatation or by multi-increment serial dilatation technique. Objectives: To compare the outcome of PCNL done by single versus serial dilatation technique with specific reference to renal access time, total operative time, stone clearance rate, postoperative haematuria and duration of postoperative hospital stay. Methods: It was a prospective interventional study with a sample size of sixty where odd number patients were included in group A (PCNL by single shot dilatation technique) & even number patients were in group B (PCNL by serial dilatation technique). After meticulous checking and rechecking, collected data were compiled and statistical analysis was done using computer based software SPSS (statistical package for social science, Version- 16) and Students t-test and Chi-square test were applied for hypothesis testing. ‘P’ value <0.05 was considered as significant. Results: Comparison between the two groups regarding stone size, stone clearance rate, postoperative haematuria and postoperative hospital stay were not statistically significant (p> 0.05). But mean renal access time in minutes (group A was 3.43 ± 1.14 and group B was 4.20 ± 1.37) and the mean operative time in minutes (group A was 91.13 ± 19.08 and group B was 101.67 ± 15.81) between the groups were statistically significant (p < 0.05). Conclusion: Percutaneous nephrostomy access can be successfully performed by single shot dilatation technique during PCNL with the advantages of shorter renal access time and total operative time. Bangladesh Journal of Urology, Vol. 23, No. 2, July 2020 p.124-128